A community farm maps back! Disputes over public urban farmland in Calgary, Alberta. Issue 1 (1st January 2021) - Barbosa Jr., Ricardo; Burns, Ryan
ABSTRACT: Geographers, cartographers, and related social scientists are increasingly locating the (geo)politics of the vernacular within volunteered geographic information, the geoweb, and other digital technologies that enable the production of new maps. We instead focus our attention on 'old' cartographic practices. We contend that map-based community activism and geopolitics continue to occur in ways that much research has left behind in its shifted attention toward digital geographies. We conceptualize vernacular counter-mapping, as practiced by Grow Calgary a community urban farm located on public land, by focusing on vernacular cartographic method and mode . We argue first that the vernacular exists not just in the production of new maps but also in the practice of altering and re-narrating existing maps, and, second, that the vernacular exists not just in the new modes of VGI and distributed/crowdsourced data production, but in the mode of leveraging official, static state maps to make legible situated knowledges.